Novel Concepts for Teaching Particle Technology - Peukert, Wolfgang; Schmid, Hans-Joachim (Chemical Engineering Education, 2002)
The introduction of particle technology in chemical engineering is discussed. The course focuses on product property approach. The course enhances the students's awareness of the whole process, the concepts for the formation of structured solids, product design and powder processing systems. Another course on particle characterization enables the students to choose an appropriate setup for arbitrary particle characterization task.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.novelc
Keywords: teaching; perticle; technology